Penerapan Teknologi Oven Pengering Cat Tipe Tertutup Dengan Isolator Aluminium Foil Pada UMKM Bengkel Otomotif - Daniel Parenden; Paulus Mangera; Cipto Cipto (CV. IRA PUBLISHING, 2026)
Paint drying in small automotive repair workshops is commonly performed at ambient conditions, resulting in long waiting times and inconsistent film formation, especially for waterborne coatings. This limits daily throughput and repeatability. This study designs and evaluates a simple low-temperature (30-40°C) closed drying oven for paint specimens with a 0.60 m3 chamber (1.2 x 1.0 x 0.5 m), a 200 W electric heater, and on-off thermostat control. An internal aluminum-foil radiant barrier is applied to reduce wall heat losses. Thermal performance is assessed using analytical heat-loss estimation and warm-up tests to a 40°C setpoint. The predicted wall heat loss decreases from 648 W (without foil) to about 97 W (with foil), yielding an effective heating power of roughly 103 W. Experiments show the oven reaches 40°C within 4-6 min and maintains the setpoint with stable cycling. Thermal efficiency improves from 31% to 85%, indicating a low-cost, energy-saving solution for practical specimen drying in SMEs.